An experimental test of the genetic consequences of population augmentation in an amphibian - Phillip G. Byrne; Aimee J. Silla (Conservation Science and Practice, 2020)
Abstract Supplementing declining populations with individuals from different populations (population augmentation) is increasingly being considered an effective way to genetically rescue threatened species. However, the general value of population augmentation remains contentious, largely because few studies have experimentally tested the genetic consequences of mixing individuals from different populations. Among amphibians, which typically display fine‐scale genetic structuring, there is a high risk that population augmentation might exacerbate population decline via outbreeding depression. Here, we use artificial fertilization techniques combined with a cross‐classified breeding design (North Carolina Type II) to investigate the fitness consequences of outbreeding in the near threatened brown toadlet (Pseudophryne bibronii). Our results revealed that outcrossed families suffered from significantly lower fertilization success, hatching success and larval survival to metamorphosis. These findings suggest that inter‐population crosses might be susceptible to genetic incompatibility and outbreeding depression. However, because genetic factors specific to one of our study populations may have caused outcrossed families to have reduced fitness, an additional breeding experiment involving full factorial crosses will be required to draw firm conclusions. Nevertheless, our findings underscore the need for caution when conducting population augmentation in amphibians. Before mixing populations that might be evolutionary distinct, we encourage conservation managers to use artificial fertilization techniques and cross‐classified breeding designs to critically assess the risk of outbreeding depression. We argue that widespread adoption of this approach will enable more rapid assessment of the risks associated with population augmentation and improve the management of threatened amphibians globally.